Effect of sunflower germination conditions for reducing phytate content and to enhancing phytase and acid phospatase activities - Agostini, Juliana da Silva; Ida, Elza Iouko (Semina: Ciências Agrárias, 2006)
The response surface methodology was applied to investigate both length of time and temperature of the sunflower germination process on the phytate reduction and to enhancig phytase and acid phosphatase activities. The hybrid (Helianthus annuus) M734 was used and the factorial design 22 with two repetitions at the central point working with two variables time and temperature at two levels, completing four experiments with two repetitions at central point were applied. Experiments were performed randomly and the germination process was carried out using a germination camera at 25ºC under fluorescent illumination during 8 days. Seeds were collected from the second day of experiment, lyophilized and ground in order to process the quantitative analysis of phytate and the enzymes activity. Results showed that the length of time and temperature were significant on the reduction of phytate amount and the occurrence of the maximum enzymes activity. The maximum phytate reduction and the acid phosphatase activity was observed at the sixth day of seed germination at 30ºC while for phytase activity the best conditions were at the fourth day at the same temperature.